Studying teachers’ knowledge by the use of multiple-choice items: the case of ”I’m not sure” - Fauskanger, Janne; Mosvold, Reidar (NOMAD Nordic Studies in Mathematics Education, 2014)
The mathematical knowledge for teaching (MKT) measures have been widely adopted by researchers in several countries. This article reports on a study on the connection between teachers’ responses to multiple-choice MKT items, and in particular where they select the suggested solution ”I’m not sure”, and their written responses to corresponding open-ended questions (long responses). The findings from our analysis of 15 teachers’ responses indicate that their long responses and their multiple-choice responses do not always correspond. Some teachers who selected ”I’m not sure” showed uncertainty also in their long responses, whereas other teachers revealed instrumental and even relational understanding of the content.